Nitrile rubber compounds with improved flex-crack resistance - Mohandas K S; Varghese S (Rubber Science, 2014)
Incorporation of reinforcing fillers is essential for enhancing of technologically important physical properties of elastomers. Various types of carbon black are highly efficient in reinforcing elastomers. Within the family of black fillers, reinforcing efficiency varies widely and this depends mainly on the particle size of the filler. For certain applications, along with reinforcement, resistance to flex-crack also has importance. In this study, conventionally used blacks namely HAF, FEF and GPF were compared for their flex-crack resistance in nitrile rubber vulcanizates. Nitrile rubber was selected since the study was aimed at developing a flex-crack resistant vulcanizate which can perform in hydrocarbon oil medium. By increasing the dosage of carbon black from 40 to 60 phr, flex-crack resistance improved up to 50 phr loading for the three fillers and this decreased thereafter. Among the fillers used, the one with the largest particle size produced the highest flex-crack resistance.
Source Year: 2012
Keywords: Acrylonitrile rubber; Acrylonitrile rubber; Fatigue; Fatigue; Flex-crack resistance; Flex-crack resistance; Particle size; Particle size; Reinforcement; Reinforcement